Reverse Fragility Index in Plastic Surgery Randomized Controlled Trials - Rodney Ahdoot, BS; Trista M. Benítez, MPH; Chien-Wei Wang, MD; Kevin C. Chung, MD, MS (Plastic and Reconstructive Surgery, Global Open)
Background:. The reverse fragility index (RFI) is a measure used to evaluate the neutrality of statistically nonsignificant findings in randomized controlled trials (RCTs). The RFI represents the minimum number of events needed to reverse a statistically nonsignificant result into a significant one. This study applied the RFI to examine the robustness of statistically nonsignificant RCTs in plastic surgery. Methods:. A systematic literature search of the 10 highest impact journals covering plastic and reconstructive surgery topics was conducted to identify RCTs published between January 2000 and March 2023. The Fisher exact test was used to calculate the RFI for each primary outcome. Bivariate analysis was performed to investigate the association of trial characteristics with the RFI. Results:. Forty RCTs that yielded 65 primary outcomes were included in the analysis with a median sample size of 76 participants (interquartile range [IQR], 49–129) and a median of 10 events (IQR, 3–22). The median RFI was 4 (IQR, 3–5), indicating that statistical significance would have been achieved if 4 participants had a change in event status. The median RFQ was 0.053 (IQR, 0.038–0.08). Most studies (21 of 40) did not perform statistical power analysis. Twelve of 40 RCTs did not report or clearly indicate loss to follow-up. Conclusions:. The findings of RCTs in the plastic surgery literature demonstrate fragility as the preservation of nonsignificant results rested on a small number of events. The RFI is a useful measure to complement the P value and examine the neutrality of null clinical trials.